Changing Pattern of World Trade and Role of Global Supply Chains: Evidences from Recent Literature - Singh, Kulwinder; Kaur, Simran; Shalu, Kumari (Gyan Management Journal, 2023)
Recent developments in the world economy have substantially increased  interdependence among nations, due to which no nation can isolate itself  completely from the rest of the world. Internationalization of production  has resulted to mutual exchange of goods, services, technologies, people  and investment, generally called as supply-chain trade. These processes  have dramatically influence structure of production networks in global  economy. Traditional domestic production networks have been replaced  by much modernized global ones. The trade that is taking place through  international networks is associated with momentous of global economic  changes. These global supply networks have several economic and non economic effects particularly on the business organization involved and  generally on the economies/nations as a whole. Trading pattern of world  economy has also experiencing changes under the influence on these supply  chains. This paper highlights the role of recent global supply chains in  changing pattern of world trade. Evidences from literature reveal that recent  global supply chains have had a significant effect on pattern of world trade  as Newly Emerging Economies (EMEs) are emerging as manufacturing  trading partners which was not even dreamt about few years back during  1970s and 1980s. Role of supply chain to make these changes incidental is  multidimensional and immense. Paper also highlights role of transnational  corporations (TNCs) in coordinating global trade through creation of global  supply chains and importance of these chains as instrument of trade policies  for firms in developing nations.
Keywords: Global Supply Chains; World Trade; Globalisation; Liberalisation; EMEs; TNCs